“The Better Part of Valour Is Discretion”: Should the IRS Change or Surrender Its Oversight of Tax-Exempt Organizations? - Mayer, Lloyd Hitoshi (Columbia Journal of Tax Law, 2016)
Recent events have highlighted the difficulties the Internal Revenue Service faces when attempting to ensure that purportedly tax-exempt organizations in fact qualify for that status. The problems in this area go much deeper than a group of IRS employees subjecting certain organizations to greater scrutiny based on their political leanings, however. For decades members of the public, the media, the academy, and Congress have criticized the limited ability of the IRS to ensure that organizations claiming exemption from federal income tax in fact deserve that categorization. Yet examples of IRS failings in this area continue to arise with depressing frequency. This is not surprising given that oversight of exempt organizations is but one of many areas that suffers from major difficulties faced by the IRS as a whole, including shrinking resources, growing responsibilities, and increasing responsibility for determinations that go beyond those necessary for revenue collection. This Article draws on tax compliance literature to explore how the current level and methods of oversight for exempt organizations could be modified to improve compliance even given the existing resource constraints. It concludes that while marginal improvements in oversight are possible, there is no silver bullet to counter the IRS’s growing inability to oversee this area. Part IV of this Article therefore turns to more radical proposals that would move the locus of oversight for exempt and particularly charitable organizations out of the IRS. The proposal that shows the most promise, but also is the most risky, would shift much of this role to a private, self-regulatory body overseen by the IRS. Given the current state of IRS oversight, this proposal deserves serious consideration.